Effect of different multipurpose tree prunings and placement method on the growth and development of rape (Brassica napus L.) - Butai, Michael Kokera (Midlands State University, 2015)
Production of vegetables in the smallholder sector of sub-Saharan Africa (SSA) is affected by poor soil fertility with nitrogen (N) being the most limiting nutrient. Continued nutrient mining without adequate replenishment has led to a corresponding decline in soil fertility and crop yields due to failure by farmers in SSA to purchase inorganic fertilisers. Leguminous multipurpose tree (MPT) prunings have widely been promoted as alternative sources of N but nutrient release is affected by type of MPT and quality attributes such as total N, total carbon(C), lignin, polyphenols and C:N ratio. The aim of this study was to evaluate various MPTs which can provide adequate N to Brassica napus L. (rape) which is a short season but high N demanding crop harvested over multiple times. An experiment was therefore, conducted at the Midlands State University to determine the yield response of rape to legume prunings of different quality. The experiment was arranged as a 2 x 7 factorial treatment structure in a randomised complete block design (RCBD) with placement method (mulching or soil incorporated) being the first factor and pruning type (Tithonia diversifolia, Gliricidia sepium, Calliandra calothyrsus, Acacia karoo, Acacia angustissima, Leucaena pallida and Leucaena trichandria) being the second factor. The tree prunings were applied at a rate to achieve 150 kg N ha-1. The crop was transplanted at 4 weeks after sowing. Data on LAI, fresh and dry weight readings as well as leaf chlorophyll readings were taken fortnightly and subjected to an analysis of variance (ANOVA). Incorporation of prunings achieved the highest total dry mass of 1,046 t ha-1 compared to mulching which had 0.580 t ha-1. The two Acacia species achieved the lowest dry mass (DM) yields while G.sepium and C.calothyrsus achieved the highest DM yields. A. angustissima and A. karoo achieved the lowest total fresh leaf yield of 1.681 and 1.910 t ha-1 respectively while L. trichandria was the highest yielding at 1.996 t ha-1 for mulched treatments. Under incorporated treatments L. trichandria and A. angustissima gave the lowest total yields of 2.206 and 2.033 t ha-1 respectively while T. diversifolia was the highest yielding at 2.377 t ha-1 fresh weight. These results showed that soil incorporation gives the highest yields for fresh and dry weight. From the results it can therefore be recommended that farmers should use T. diversifolia and L. trichandria prunings over the Acacia species prunings for high fresh weight yields.